2021
DOI: 10.1021/acsmaterialslett.1c00291
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrrole-Bridged Bis(oxa[5]helicene)-Based Molecular Semiconductor for Efficient and Durable Perovskite Solar Cells: Microscopic Insights

Abstract: Exotic organic semiconductors based on helicenes are attractive because of their peculiar topology-related optoelectronic properties and good solution-processability. We herein construct pyrrole-bridged bis­(oxa[5]­helicene) and further employ it as the π-linker of a solution-processable molecular semiconductor (DOP-OMeDPA) with improved hole mobility and glass transition temperature compared with its oxa[5]­helicene counterpart. A solution-processed, doped semiconducting composite of DOP-OMeDPA presents high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Beyond chiroptical properties the high solubility of helicenes in organic solvents (compared to planar acenes), coupled with their excellent thermal stability has led to a wider array of optoelectronic applications, including as hole-transport materials in photovoltaic devices. 26–28…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond chiroptical properties the high solubility of helicenes in organic solvents (compared to planar acenes), coupled with their excellent thermal stability has led to a wider array of optoelectronic applications, including as hole-transport materials in photovoltaic devices. 26–28…”
Section: Introductionmentioning
confidence: 99%
“…Beyond chiroptical properties the high solubility of helicenes in organic solvents (compared to planar acenes), coupled with their excellent thermal stability has led to a wider array of optoelectronic applications, including as hole-transport materials in photovoltaic devices. [26][27][28] Thermally activated delayed fluorescence (TADF) materials have become increasingly attractive as sensors, 29 in lasers, 30 photodetectors, 31 photocatalysis 32 and bioimaging 33 as well as both emitters and hosts in organic light-emitting diodes (OLEDs) 34 due to their ability to harvest 100% of electrically generated excitons to generate light. This is accomplished by conversion of triplet excitons into singlets via reverse intersystem crossing (RISC) [34][35][36][37][38] enabled by their small S 1 -T 1 energy gap, DE ST .…”
Section: Introductionmentioning
confidence: 99%
“…Helicenes are chiral; as a result, they are expected to have specific functionalities. Recently, helicenes have been widely applied in various fields [ 1 , 2 , 3 , 4 , 5 ], such as organic semiconductors [ 6 , 7 , 8 , 9 , 10 ], asymmetric catalysis [ 11 , 12 , 13 , 14 , 15 , 16 ], and molecular recognition [ 17 , 18 , 19 , 20 , 21 , 22 ], due to their diverse functionalities in materials. Many studies have also been reported on self-assembly phenomena at metal surfaces [ 23 , 24 , 25 , 26 ] caused by interactions with the π-orbitals of helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…A handful of studies are available for other types of devices, such as organic light emitting diodes [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ], organic solar cells [ 57 , 58 , 59 ], and hybrid DSSC [ 60 ] and perovskite solar cells [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Introductionmentioning
confidence: 99%